Beef Cattle Farming Strategy in Baluran National Park - Azizah, Siti; Alamanda, Zazin F.; Djunaidi, Irfan H.; Qurbani, Indah Dwi; Rachmawati, Achadiah; Fajriani, Sisca (International Journal of Multidisciplinary Approach Research and Science, 2024)
Sidomulyo Hamlet, Sumberwaru Village, which serves as buffer zones of Baluran National Park, has 2,220 beef cattle as a potential economical source. At the same time, the beef cattle farming business's potential threatens Baluran National Park's existence due to being grazed illegally. The condition urges an efficient strategy so cattle farming can develop without disturbing the conservation zone of the national park. The study's objective was to find out the characteristics of beef cattle farmers in Sidomulyo Hamlet and to determine a strategy to improve beef cattle farming efficiency in Sidomulyo. The research was conducted in Sidomulyo Hamlet, Sumberwaru Village, from 1st June to 18th July 2022. The research method used a descriptive quantitative method with a SWOT analysis. The respondents were 72 cattle farmers. The research results showed that most of the cattle farmers in Sidomulyo are male, aged between 41-50 years old; the education level is mostly Elementary School, 11-20 years of cattle farming experience, and livestock ownership scale under 4 Animal Unit (AU). Increasing cattle farming efficiency is an SO strategy that supports aggressive growth: 1) Optimizing land use by planting forage. 2) Optimization of farmers' potencies and the availability of resources. 3) Cooperate with government and academicians to increase farmers’ knowledge and skill. 4) Application of feed processing and livestock manure technology.